Prevalence of Clinical Diagnosis of Temporomandibular Disorders Based on DC/TMD, Axis I in Adult Ukrainians of Different Gender and Age - Klochan, Svitlana M.; Osnach, Roman H.; Savchenko, Mykola V.; Chaikovskyi, Ihor H. (International Journal of Psychosocial Rehabilitation, 2020)
The article presents the results of the study, the purpose of which was to establish and analyze the prevalence of clinical diagnosis of Temporomandibular disorders (TMD) according to the Diagnostic Criteria for TMD, Axis I (DC/TMD, Axis I) among patients seeking medical advice. Gender and age distribution of TMD clinical diagnoses, as well as the nature and incidence of TMD combined diagnoses, were also of importance for the authors. To form homogeneous symptomatic groups, the DC/TMD Axis I clinical diagnostic protocol was used, which is a standardized tool for TMD diagnosis for research and clinical purposes. Based on the study, it was established that the use of unified diagnostic tools for TMD diagnosis, such as the DC/TMD, increased the consistency between independent studies of the prevalence of clinical diagnoses of TMD. The use of the DC/TMD allowed the obtaining and comparison of own TMD prevalence data with independent, identical studies conducted in different countries. The novelty of the article is the study of the prevalence of clinical diagnoses of TMD among the Ukrainian population, based on the use of the DC/TMD. The practical value of the study is due to the need to obtain data using the unified DC/TMD.